DISEÑO DE ACTIVIDADES, PROCEDIMIENTOS, POLÍTICAS Y FLUJOGRAMAS PARA EL DEPARTAMENTO COMERCIAL, FINANCIERO Y RECURSOS HUMANOS DE “AUTOSHOPPING” DE LA CIUDAD DE LOJA - Calva Paucar, Jessica Lizbeth (2019)
The work of dissertation named: DESIGN OF ACTIVITIES, PROCEDURES, POLICIES AND FLOWCHARTS FOR THE COMMERCIAL, FINANCIAL, AND HUMAN RESOURCE DEPARTMENT OF “AUTOSHOPPING” OF THE CITY OF LOJA, it was based on the development of activities, procedures, policies and flowcharts based on the review of the manual of functions of the company with the purpose of improving its company organization. To comply with the objectives an analysis was made on the activities of the manual of functions of the company to determine the requirements, for the design of graphics considering the flaws of the activities that the employees do; the result with which the principal procedures, policies, and flowcharts are determined, policies and flowcharts that are necessary for the adequate function of the company. Different administrative and operational activities were proposed which were designed and analyzed in the manual of functions where activities were designed for the commercial departments which consists of the head of sales, vendors, warehouse worker, and auto mechanic. This department highlights its purchases and sales because this company is dedicated to the purchasing and selling of automotive accessories. Procedures geared towards the activities that each area and department were designed which make up the autoshopping company, so this way the different activities are made in a coordinated way and with logical sequence for the timely attention and achieving its company obligations, so that security is brought by the department that it has as a responsibility. Flowcharts were designed for 5 each commercial, financial, and human resource department, this way the procedures that were designed for each area are met, also to be able to express in a graphic and schematic way each activity and function letting the manager and employees organize themselves more efficiently and effectively keeping in mind the order of functions. Finally, policies geared towards each department were designed conforming with the autoshopping company letting the obligations and expectations of the company known. The contribution of the design of the activities, procedures, flowcharts and policies that were planted, allows that the company become more organized, allowing employees know the functions that they must do in their hour of labor keeping in mind its organizational structure to be more organized